ANALISIS KEBUTUHAN BAHAN AJAR MATEMATIKA BERBASIS KEMAHIRAN MATEMATIS DI MADRASAH IBTIDAIYAH - Laely Farokhah; Tatang Herman; Zaenal Abidin; Riduan Febriandi; Muhammad Zulfadhli (Department of Pendidikan Guru Madrasah Ibtidaiyah Universitas Islam Negeri Alauddin Makass, 2022)
Abstract This research aimed to describe the need to analyze mathematics teaching materials based on mathematical proficiency in Madrasah Ibtidaiyah. Qualitative research was used in this research. The research was conducted in one of the Private Madrasah Ibtidaiyah in South Tangerang, Indonesia. The subject consisted of two mathematics teachers. The data collected through interview and documentation techniques consisted of curriculum and mathematics teaching materials. The data were analyzed using triangulation consisting of data reduction, presentation, and conclusion and verification. The result showed that the need analysis of mathematics teaching materials consisted of: (1) the curriculum of mathematics needed to be arranged about the sequence of materials, (2) teachers needed mathematics teaching materials in various types, and (3) the mathematics concepts based on mathematical proficiency in teaching materials needed to be improved. These results can be a reference for developing teaching materials based on mathematical proficiency for mathematics teaching and learning.